Chemical compositional analysis of soil fulvic acids using Fourier transform ion cyclotron resonance mass spectrometry. (28th May 2020) - Ikeya, Kosuke; Sleighter, Rachel L.; Hatcher, Patrick G.; Watanabe, Akira
Abstract : Rationale: Soil fulvic acids (FAs) are considered to be a highly reactive pool of soil organic matter. The functions of FAs are related to their chemical structures, the details of which are largely unidentified. To better understand them, Fourier transform ion cyclotron resonance mass spectrometry (FTICR‐MS) must be a useful but generally unused tool. Methods: The structural properties of the components of five FA samples from a variety of soils were determined using FTICR‐MS with negative‐mode electrospray ionization. The peaks were assigned to molecular formulae, which were categorized into seven compound groups based on the H/C–O/C van Krevelen diagram. Ramp 13 C cross polarization/magic angle spinning nuclear magnetic resonance (NMR) spectra with phase‐adjusted spinning side bands were also recorded to estimate the C composition. Results: From FTICR‐MS, molecular formulae were assigned to 1746–2605 peaks across the m/z range of 200–700. Those aligned in the lignin‐like, tannin‐like, and condensed aromatic regions of the van Krevelen diagram accounted for 49–58%, 4–20%, and 18–39% of the total peak magnitude, respectively. The proportion of the summed peak magnitudes that were detected in the lignin‐like and condensed aromatic regions correlated positively to the aromatic C% as estimated by 13 C NMR. From Kendrick mass defect analysis using a carboxyl group, 94 molecular formulae were assigned to condensed aromatic acids, of which the maximum ring number was 4–7, as potential structures. Conclusions: A high proportion of lignin‐like formulae and condensed aromatics, including those probably condensed aromatic acids with small ring numbers, as well as the existence of tannin‐like formulae, which were generally lacking in soil humic acids, was suggested as a common feature of soil FAs. Abstract : □□□